2006
DOI: 10.1093/erae/jbl013
|View full text |Cite
|
Sign up to set email alerts
|

Local polynomial fitting and spatial price relationships: price transmission in EU pork markets

Abstract: SummaryWe study price transmission processes within EU pork markets after the implementation of the EU single market in 1993. We compare results derived from nonparametric regressions with those obtained using alternative nonlinear threshold models. Both techniques support the hypothesis that prices are transmitted across spatially separate EU pig markets and provide evidence for asymmetric price adjustments. They also suggest the existence of a range of price differentials where equilibrating price adjustment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
64
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 49 publications
5
64
0
1
Order By: Relevance
“…The relatively low overall degree of dependence, and, more importantly, the evidence in favor of asymmetric price co-movements, suggest that the three principal EU olive oil markets cannot be thought of as one great pool. In this regard, the findings of the present work are in line with those of Serra et al (2006), who reported evidence of asymmetric price transmission in four major EU pork markets, and Fousekis (2007), who found considerable segmentation in 15 geographically separated markets of the EU.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The relatively low overall degree of dependence, and, more importantly, the evidence in favor of asymmetric price co-movements, suggest that the three principal EU olive oil markets cannot be thought of as one great pool. In this regard, the findings of the present work are in line with those of Serra et al (2006), who reported evidence of asymmetric price transmission in four major EU pork markets, and Fousekis (2007), who found considerable segmentation in 15 geographically separated markets of the EU.…”
Section: Discussionsupporting
confidence: 92%
“…Under spatial market segmentation, profitability opportunities are not fully exploited resulting into efficiency losses (e.g. Asche et al, 1999;Serra et al, 2006;Reboredo, 2011). 4 C. Emmanouilides et al / Span J Agric Res (2014) 12(1): 3-14 Although market globalization, in general, and food market integration in particular, has been an issue of great importance for both economists and policy makers, the number of recent formal studies on the price interrelationships and/or on the validity of the LOP for spatial EU agri-food markets has been rather small.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the evidence of non-linear price adjustment in the ex-vessel-wholesale market channels suggests the existence of some barriers to free trade (Serra et al, 2006). Such barriers might include high transaction costs and imperfect information.…”
Section: Discussionmentioning
confidence: 99%
“…In an equilibrium concept, in a well-functioning market, the price shocks occurring in one market cause responses in other markets. As a consequence, prices of the same products in two separate locations will differ by transport costs from the cheapest market to the most expensive one (Serra and Goodwin, 2006).…”
Section: Introductionmentioning
confidence: 99%